Sistem Pendukung Keputusan Penerimaan Bonus Karyawan menggunakan Metode TOPSIS - Sama, Hendi; Permata, Dwi Ninda (Telcomatics, 2023)
Decision support systems determine employees who have a high priority in receiving bonuses according to criteria set by the company. The decision system is only to help provide decision suggestions more quickly, accurately, and reduce the level of errors during the decision process. The bonus system that employees receive as a design strategy for each employee can work even more. The application of the TOPSIS method has the smallest distance from the positive ideal solution and has the largest distance from the negative ideal solution to produce the ideal solution in the form of a preference value. The results of this study indicate a decision support system that can determine the level of eligibility of an employee to receive bonuses. The criteria used are attendance, behavior, loyalty and work results. As a consideration for the decision makers such as the head of the division, manager. To improve the quality of employee appraisals, in order to be able to give bonuses properly by paying attention to the determination of criteria and provide assessment criteria that are appropriate to increase employee performance motivation.